SUBJECTS GRIEFED BY SUICIDE DURING THE COVID-19 PANDEMIC: A LITERATURE REVIEW - Gabriea Laranjeira Bezerra, Ana; Batista De Souza Neta, Marta (Health and Society, 2023)
Suicide is considered a public health problem. With COVID-19, citizens were forced to remain in social isolation, to prevent the spread of the pathogen. The compulsory restrictions provoked several reactions, interfering in the grieving process, especially when the death was self-inflicted, involving judgments, stigmas, and taboos, which directly interfered in the grieving process. We carried out a bibliographic survey of articles already published about suicide grief during the pandemic of COVID-19, aiming to spread knowledge and awareness about the grief experienced by subjects who lost someone to suicide, and how a pandemic can cause suicidal behavior. The literature review, conducted in February 2023. Publications indexed in the Virtual Health Library (VHL), in the Latin American and Caribbean Literature on Health Sciences (LILACS), and in the Scientific Eletronic Library Online (SCIELO). The descriptors were: Suicide, Covid, Mourning. To filter the search and as inclusion and exclusion criteria, the period from 2019 to 2023 and relevance to the theme were selected. It is necessary to reflect on how the alteration of the routine, financial and material losses, and the lack of emotional support suppressed by social distancing were consequences and predictors for mental illness, provoking suicidal behavior and leading to mourning by suicide during the pandemic, to be traumatic and painful, with reverberations for the post- pandemic. Through interventions, with psychosocial support, it is necessary to reflect on the impact of pandemics, where pandemics can give rise to traumatic and complicated bereavements, and the implementation of governmental measures that can support the bereaved.